2013
DOI: 10.1148/radiol.13130058
|View full text |Cite
|
Sign up to set email alerts
|

Triple-Negative and Non–Triple-Negative Invasive Breast Cancer: Association between MR and Fluorine 18 Fluorodeoxyglucose PET Imaging

Abstract: Purpose:To assess the relationship between parameters measured on dynamic contrast material-enhanced (DCE) magnetic resonance (MR) imaging and fluorine 18 fluorodeoxyglucose (FDG) positron emission tomography (PET)/computed tomography (CT) in primary invasive breast cancer. Materials and Methods:This HIPAA-compliant study was a retrospective review of medical records and therefore approved by the institutional review board without the requirement for informed consent. Patients with a diagnosis of invasive brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 23 publications
1
11
1
Order By: Relevance
“…Breast cancer is a heterogeneous disease with a broad range of therapeutic responses, recurrence risk, and overall prognosis [ 1 ]. Predicting the prognosis of breast cancer is very important to determine the direction of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is a heterogeneous disease with a broad range of therapeutic responses, recurrence risk, and overall prognosis [ 1 ]. Predicting the prognosis of breast cancer is very important to determine the direction of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies analyzed correlation of CA enhancement patterns on MR images with histopathological findings and tumor angiogenesis [63], [64], and with PET imaging[65]. This study analyzed error propagation of SQ parameters in three types of SI-time courses, selected on the basis of these published findings, to investigate these curve shapes' preference for robust calculation of SQ parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is the most sensitive method for breast cancer detection. It is also useful for detection and characterization of TNBC [6,7,8]. Several studies have reported the MRI features of TNBC, and describe some sensitive MRI features more frequently seen in TNBC than in other subtypes of breast cancer, including rim enhancement, intratumoral high signal on T2-weighted images, and peritumoral edema, which appear to be related to poor prognosis [1,2,6,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Standardized uptake value (SUV), a semi-quantitative measurement of FDG uptake, has been reported to be a prognosis predicting factor for TNBC [12,13,14]. TNBC shows higher SUVmax than other subtypes of breast cancer [4,8]. Dogan et al [4] suggested that the high SUVmax of TNBC is caused by increased glycolysis due to the high proliferation rate of TNBC.…”
Section: Introductionmentioning
confidence: 99%